2011
DOI: 10.1016/s1701-2163(16)35048-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Liver Function Tests as Predictors of Adverse Maternal Outcomes in Women With Preeclampsia

Abstract: Objectives: To evaluate whether (1) the absolute magnitude of liver function test values, (2) the percentage change in liver function test values over time, or (3) the rate of change in liver function test values over time predicts adverse maternal outcomes in women with preeclampsia Methods:We used data from the PIERS (Pre-eclampsia Integrated Estimate of RiSk) study, a prospective multicentre cohort study assessing predictors of adverse maternal outcomes in women with preeclampsia Women with at least one l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 24 publications
5
36
1
1
Order By: Relevance
“…These findings were in accordance with a study done by Qublan et al [13] and Kozic et al [14]. They concluded that serum LDH can be a useful marker for the prediction of adverse outcome of pregnancy in severe preeclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were in accordance with a study done by Qublan et al [13] and Kozic et al [14]. They concluded that serum LDH can be a useful marker for the prediction of adverse outcome of pregnancy in severe preeclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…Liver tests cannot exclusively be used to gauge clinical decisions, as the presence of normal liver enzymes does not exclude disease ( 53,54 ). An expectant approach is advised until aft er 34 weeks gestation to limit fetal morbidity ( 55 ).…”
Section: Preeclampsia and Eclampsiamentioning
confidence: 99%
“…The odds of having an adverse maternal outcome were higher in women with any abnormal liver function test than in women with normal results [11].…”
Section: Discussionmentioning
confidence: 85%